Efektivitas Penggunaan Tempat Sampah Terpilah terhadap Ketepatan Membuang Sampah Siswa di SDN Ciherang - Muhammad Rifki; Anna Maria Oktaviani; Muhamad Abdul Roji (STKIP Subang, 2026)
Waste management issues represent a serious challenge in Indonesia, exacerbated by population growth, urbanization, and the suboptimal level of community participation in waste segregation and policy implementation. In this context, early education at the elementary school level is recognized as a fundamental instrument for instilling awareness and responsible habits related to waste management. This study aims to investigate the effectiveness of using segregated waste bins, particularly those modified with sound or visual features, in improving students’ waste disposal accuracy at SDN Ciherang. This approach is based on the concept that segregated waste bins can function as constant pedagogical tools by providing visual cues and feedback that encourage positive behavioral change. This study employed a quasi-experimental design using a Nonequivalent Control Group Pretest–Posttest approach involving two groups of students at SDN Ciherang. Quantitative data were collected through behavioral observations and waste audits to measure segregation accuracy, while qualitative data were obtained through questionnaires and interviews to understand students’ perceptions and motivations. The hypothetical results indicate a significant increase in waste segregation accuracy in the experimental group using the modified waste bins, from 45.2% to 88.5%, whereas the control group showed no significant change. The sound and visual features of the waste bins hypothetically contributed to increased student enthusiasm and understanding, as well as positive changes in waste segregation behavior. It is concluded that the use of segregated waste bins modified with sound or visual features is hypothetically highly effective in improving proper waste disposal and fostering environmental awareness among elementary school students. These findings suggest that interactive infrastructure design can serve as an important component of a comprehensive environmental education strategy.